Reshaping Norms : A New Way Forward - World Bank (Washington, DC: World Bank, 2022)
South Asia’s growth rate has returned to pre-pandemic levels. However, the uneven recovery from the pandemic has left countries in South Asia with multiple policy challenges, which are exacerbated by the impact of the war in Ukraine. While several countries are navigating rising inflation and growing difficulties to finance fiscal deficits and trade deficits, the region must also chart a new way forward to address rising inequality, unleash new growth potential, and accommodate an energy transition. To reshape their economies, the region cannot avoid redesigning tax systems, increasing competition, and challenging vested interests and existing gender norms. This issue of the South Asia Economic Focus, describes recent economic developments, analyzes the economic impact on South Asia of the war in Ukraine, presents growth forecasts, provides risk scenarios, and concludes that reshaping economies goes hand in hand with reshaping norms.